(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
Hepatorenal syndrome (HRS) is a renal dysfunction without morphological changes that occurs in the context of severe liver failure and portal hypertension, and is frequently associated with liver cirrhosis. In recent years, the increasing frequency of renal failure associated with liver diseases and the clinical significance of new markers such as cystatin C have sparked scientific interest.